MATERIALISME DALAM PERSPEKTIF KITAB TAFSIR AL-AZHAR KARYA BUYA HAMKA - Muhammad Khudzaifah; Halimatussa’diyah Halimatussa’diyah; M. Arfah Nurhayat (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
The purpose of this study is to clarify the materialism of the book Tafsir Al-Azhar by Buya Hamka. Tafsir Al-Azhar is one of the interpretations of the sons of the Indonesian nation which is still very influential today, one of the interpretations that is considered very representative for expressing understanding in various disciplines, both religious and non-religious, and socio-historical. Islam is a universal teaching, there is no prohibition for a person not to be able to look for material while living in this world, but also not to forget about the afterlife. At this time material is the main reference in the social ladder in life, rank and wealth are very appropriate benchmarks for current conditions. living like this, a materialist and stylish mindset arises as a place for existence. This materialist mindset causes humans to always focus on the world and indirectly loves wealth excessively, causing a loss of self-esteem, social attitudes and rules that serve as guidelines. The materialism that the author means is a lifestyle that is excessive in worldly affairs, especially material things, so that it neglects the purpose of life, so the writer tries to understand the verses of materialism through Buya Hamka's interpretation. This study uses the Maudhu'i method, the form of research is library research. The primary data in this study is Al-Azhar Interpretation and secondary data in the form of interpretations, hadiths and supporting books and journals related to the material. The findings of this study are: a lifestyle that accumulates wealth, counts, spends extravagantly, boasts and loves wealth excessively is a characteristic of a materialistic attitude, when this attitude appears in social life, a lack of social solidarity and the emergence of individualistic attitudes such as arrogant and arrogant that is rampant so that it has an impact on aspects of social life.